EVALUASI KINERJA STRUKTUR BANGUNAN DENGAN METODE PUSHOVER ANALYSIS PADA GEDUNG RUMAH SAKIT STROKE NASIONAL BUKITTINGGI - Elvi Reyani; Ishak Ishak; Surya Eka Priana (Ensiklopedia Research and Community Service Review, 2021)
Earthquake phenomena are natural phenomena that greatly affect buildings, especially high-rise buildings. Planning of earthquake-resistant building structures is very important in Indonesia, considering that most of the area is located in earthquake areas with moderate to high intensity. Buildings in earthquake-prone areas must be designed to be able to withstand earthquakes. The latest planning trend is performance based seismic design, which utilizes computer-based non- linear analysis techniques to analyze the inelastic behavior of structures from various ground motion intensities (earthquakes), so that their performance can be known in critical conditions. Further action can be taken if it does not meet the required requirements. The purpose of this study was to determine the pushover analysis procedure to evaluate the performance of the building structure and to determine the pattern of the collapse of the building structure after being analyzed by pushover. This study uses the Static Pushover Analysis method with reference to the displacement coefficient method (FEMA 356, 2000). The lateral load used is the result of an equivalent static analysis which is carried out monotonically in one direction. Research shows that there are several conclusions. First, the displacement of the maximum pushover result (δmax) in the XZ direction, which is in step-7, is greater than the displacement target (δt), with a figure of 61541.4681 mm > 58.212 mm. Second, the displacement of the maximum pushover result (δmax) in the YZ direction, namely in step-5, is greater than the displacement target (δt), with a figure of 10450.54 mm > 58.212 mm. Third, the evaluation in the XZ direction is still safe even though max > t, because all beam elements in the portal appear plastic hinges with levels A-B which are still elastic, all marked in pink. The distribution of plastic hinges that occur at all steps shows that no structural member exceeds the performance limit so that it can be said that the performance of the structural component is in a safe condition. Fourth, the structural members in the YZ direction are also safe because max > t and the plastic hinge distribution scheme shows the structural members marked in pink with levels A-B. Keywords: pushover, non-linear, plastic hinge